E-018 A novel 8fr aspiration catheter significantly increases the first pass effect in comparison with industry standard 6fr devices in an in-vitro human vasculature model. (4th August 2020) - Fitzgerald, S; Ryan, D; Mullins, L; Thornton, J; Nogueira, R
Abstract : Introduction/Purpose: Achieving complete reperfusion from a single mechanical thrombectomy attempt, termed First Pass Effect (FPE), is associated with significantly improved outcomes. Increasing the lumen of aspiration catheters to 6Fr has previously been shown to increase the reperfusion rates in comparison to smaller lumen catheters. We evaluated the performance of a novel large bore (0.088'' ID) 8Fr aspiration catheter (Millipede 088, Perfuze Ltd.) and compared its performance against current industry standard 6Fr aspiration catheters (ACE68, Penumbra and SOFIA Plus, Microvention) in an in-vitro human vasculature model. Methods: Following National University of Ireland Research Ethics committee approval human whole blood and platelet donations were obtained from the Irish Blood Transfusion Service. Three clot analogue phenotypes representative of clots retrieved from patients were created; Red Blood Cell-Rich, Mixed and Fibrin/Platelet-Rich. Histopathological analysis was performed using Martius Scarlet Blue (MSB) staining to confirm clot composition. The in-vitro model comprised a peristaltic pump, aortic arch and circle of Willis. Flow rates and pressure were controlled to replicate in-vivo conditions. Clot analogues of each phenotype were inserted into the ICA and lodged under pulsatile flow. Clot volume was optimized to mimic the clinical scenario; 10 mm clots reliably lead to a Distal M1+MCA Bifurcation Occlusion and 20 mm clots reliably lead to an ICA-T + Proximal M1 occlusion covering both the Posterior Communicating Artery and Anterior Cerebral Artery. Five replicates of each test were performed. Endpoints were FPE and Second Pass Reperfusion Success (>90% Retrieved). Results: Histological composition was confirmed as RBC-Rich (RBCs:92.9%, WBCs:0.1%, Fibrin/Platelets:7.0%), Mixed (RBCs:79.7%, WBCs:0.3%, Fibrin/Platelets:20.0%) and Fibrin/Platelet-Rich (RBCs:51.8%, WBCs:0.3%, Fibrin/Platelets:47.9%). The 8Fr (Millipede 088) catheter performed better for each clot phenotype and in both occlusion locations (ICA-T & M1) compared to the 6Fr (0.068'' & 0.070'' ID) devices. In 10 mm M1+Bifurcation occlusions the 8Fr catheter achieved 100% FPE compared to an average of 40% in 6Fr devices (p>0.001*). In longer 20 mm ICA-T+Proximal M1 occlusions the Millipede 088 achieved 100% removal success within two passes in each clot phenotype compared to an average of 27% in the 6Fr devices (p>0.001*). Conclusions: A novel 8Fr aspiration catheter demonstrates superiority over 6Fr aspiration catheters for each clot phenotype at the most common sites of occlusion in an in-vitro model. Disclosures: S. Fitzgerald: 1; C; Perfuze Ltd. D. Ryan: None. L. Mullins: 4; C; Perfuze Ltd. 5; C; Perfuze Ltd. J. Thornton: 2; C; Perfuze Ltd. 4; C; Perfuze Ltd. R. Nogueira: 2; C; Perfuze Ltd. 4; C; Perfuze Ltd.